Fission yeast telosomes: non-canonical histone-containing chromatin structures dependent on shelterin and RNA. Issue 17 (10th July 2018) - Greenwood, Jessica; Patel, Harshil; Cech, Thomas R; Cooper, Julia Promisel
Abstract: Despite the prime importance of telomeres in chromosome stability, significant mysteries surround the architecture of telomeric chromatin. Through micrococcal nuclease mapping, we show that fission yeast chromosome ends are assembled into distinct protected structures ('telosomes') encompassing the telomeric DNA repeats and over half a kilobase of subtelomeric DNA. Telosome formation depends on the conserved telomeric proteins Taz1 and Rap1, and surprisingly, RNA. Although yeast telomeres have long been thought to be free of histones, we show that this is not the case; telomere repeats contain histones. While telomeric histone H3 bears the heterochromatic lys9-methyl mark, we show that this mark is dispensable for telosome formation. Therefore, telomeric chromatin is organized at an architectural level, in which telomere-binding proteins and RNAs impose a unique nucleosome arrangement, and a second level, in which histone modifications are superimposed upon the higher order architecture.